2016
DOI: 10.1007/s11368-016-1427-0
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China

Abstract: Purpose Knowledge of archaeal communities is essential for understanding of the mechanism of carbon and nitrogen cycle in the mangrove sediment ecosystem. Presently, little is known about archaeal communities in the Dongzhaigang mangrove sediments. This study aimed to characterize the archaeal communities in sediments of different mangrove stands and to find out the correlations between archaeal communities and the environmental factors of sediments.Materials and methods Sediment samples were collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
12
2
Order By: Relevance
“…MF, MMA, MM, and MS were the four dominant methanogen lineages identified in the current study. This was consistent with previous 16S rRNA gene and mcrA sequencing-based identification of Methanomicrobiales and Methanosarcinales in coastal sediments [53][54][55]. Mangrove sediments in the Futian Natural Reserve are characterized by high sulfate concentrations [49], suggesting that adaptation to high salinity is important for mangrove dwelling.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…MF, MMA, MM, and MS were the four dominant methanogen lineages identified in the current study. This was consistent with previous 16S rRNA gene and mcrA sequencing-based identification of Methanomicrobiales and Methanosarcinales in coastal sediments [53][54][55]. Mangrove sediments in the Futian Natural Reserve are characterized by high sulfate concentrations [49], suggesting that adaptation to high salinity is important for mangrove dwelling.…”
Section: Discussionsupporting
confidence: 90%
“…According to metatranscriptomic analysis in the current study, MMA were the most active group in all layers, suggesting that MMA are well adapted to the fluctuating environment of mangrove sediments. Indeed, prevalence of Methanomassiliicoccales in coastal sediments has been reported [31,54], indicating their importance for methane production in natural environments. MMA MAGs contained genes encoding oligo-and monosaccharide transporters, which might illustrate adaptation to a heterotrophic lifestyle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial communities in the rhizospheres of Avicennia schaueriana and Laguncularia racemosa and archaeal communities in the rhizospheres of R. mangle and L. racemosa from Brazil showed some differences in their composition, although the main variation was between the rhizosphere of either mangrove tree and the bulk sediment communities [ 24 , 25 ]. Archaeal communities were also studied in mangroves from China, and differences were found between communities associated to K. candel or Bruguiera gymnoihiza and those associated to L. racemosa or Sonneratia apetala mangroves [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove trees can have different impacts on soil archaeal and bacterial communities through alteration of the soil microenvironment such as changes in the content of organic matter or other sediment characteristics [ 22 , 23 ], root exudates [ 24 , 25 ], and litter inputs [ 26 ]. Moreover, recent studies suggested that mangrove plants could be important factors controlling the activity, abundance, and community structure of ammonia oxidizers [ 14 , 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Woesearchaeota is abundant in mangrove sediments in some particular sites, e.g., in the mangrove sediments of Daya Bay (China), and Dongzhaigang (China), accounting for 10-27% of the total archaea (Li et al 2016;Zhang et al 2018). Lokiarchaeota, formerly named MBG-B (Marine Benthic Group B) and DSAG (Deep Sea Archaeal Group), are also important components of mangrove sediments, accounting for 2-15% of the total archaea (Fig.…”
Section: Diversity and Distribution Of Archaea In Mangrove Wetlandsmentioning
confidence: 99%